Education Psychology and Learning Performance: Does Mental Skills and Mental Techniques influences Learning Performance? A Survey Study on Indonesian Educational Institutions - Azhar Aziz; Endang Haryani; nurmaida irawani siregar (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The prime objective of this study is to investigate the role of education psychology in learning performance of students. To address this objective, cognitive aspect of education psychology is preferred in relation to the learning behavior and learning performance of students among the higher educational institutions of Indonesia. Although, education psychology remained under discussion in literature, however, earlier studies have not considered the cognitive aspect of education psychology in the presence of learning behavior and learning performance of students. A survey is carried out among the higher educational institutions of Indonesia. Data collection is made by using questionnaire. After analyzing the data through artistical tool, it is found that; education psychology has major importance among the educational institutions. As education psychology has positive role to promote learning performance of students. Cognitive aspects of education psychology such as foundation skills, interpersonal skills, mental imagery and self-task has important contribution to achieve positive student behavior and higher learning performance.